2014
DOI: 10.1186/2045-824x-6-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of RNA interference in the developmental separation of blood and lymphatic vasculature

Abstract: BackgroundDicer is an RNase III enzyme that cleaves double stranded RNA and generates functional interfering RNAs that act as important regulators of gene and protein expression. Dicer plays an essential role during mouse development because the deletion of the dicer gene leads to embryonic death. In addition, dicer-dependent interfering RNAs regulate postnatal angiogenesis. However, the role of dicer is not yet fully elucidated during vascular development.MethodsIn order to explore the functional roles of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
(69 reference statements)
1
3
0
Order By: Relevance
“…However, consistent with a recent report 16) , the endothelial Dicer homozygous KO mice, generated by cross-breeding of Tie2-Cre mice and Dicer flox mice, also showed embryonic lethality. Gauvrit et al reported that the endothelial Dicer homozygous KO mice displayed impairment of blood and lymphatic vasculature separation, hemorrhage and edema from E12.5 to E14.5 16) . These data highlighted that the Dicer-mediated miRNA processing in ECs is essential for normal embryonic development.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, consistent with a recent report 16) , the endothelial Dicer homozygous KO mice, generated by cross-breeding of Tie2-Cre mice and Dicer flox mice, also showed embryonic lethality. Gauvrit et al reported that the endothelial Dicer homozygous KO mice displayed impairment of blood and lymphatic vasculature separation, hemorrhage and edema from E12.5 to E14.5 16) . These data highlighted that the Dicer-mediated miRNA processing in ECs is essential for normal embryonic development.…”
Section: Discussionsupporting
confidence: 77%
“…However, we could not obtain homozygous KO offspring. It has recently been reported that crossbreeding Tie2-Cre and Dicer fl/fl mice results in lethality due to developmental vascular dysfunction 16) . We confirmed that the inactivation of Dicer in ECs results in embryonic lethality during the developmental stage.…”
Section: Generation Of Endothelial Cell-specific Dicer Ko Micementioning
confidence: 99%
“…To perform whole-mount immunostaining in mouse 62 , tissues were fixed overnight in 4% PFA and blocked overnight in blocking buffer (TSA blocking reagent, Perkin Elmer). Tissues were then incubated for 2 days at 4 °C with biotinylated antibodies in blocking buffer followed by biotin-streptavidin-horseradish peroxidase amplifications using the Vectastain-ABC Kit (Vector labs).…”
Section: Methodsmentioning
confidence: 99%
“…*P Ͻ 0.05 and **P Ͻ 0.01 vs. control (Con). have demonstrated that mice deficient in conventional and EC-specific Dicer, a ribonuclease essential for miRNA processing, exhibit abnormal vascular development and embryonic lethality (17,45), suggesting that Dicer-mediated miRNA biogenesis is an essential component of normal development and embryonic angiogenesis. Previous studies have shown that each miRNA belonging to miR-23 clusters is upregulated in ECs by angiogenic conditions such as VEGF stimulation, ischemia, and laser-induced choroidal neovascularization, and these miRNAs have been implicated in angiogenesis in vitro and in vivo (16,37,47).…”
Section: Discussionmentioning
confidence: 99%